Acceptability and Antioxidant Activities of Jelly Drink Ginger (Zingiber officinale R.), Curcuma (Curcuma xanthorriza R.) and Turmeric (Curcuma longa L.) Extract as A Healthy Drink Alternative for People with Hypercholesterolemia - Ika Rosita Rahmawati; Asrul Bahar (International Journal on Food, Agriculture and Natural Resources, 2023)
This study aims to (1) determine the acceptability of ginger, curcuma and turmeric extract jelly drinks as an alternative healthy drink for people with hypercholesterolemia;(2) Knowing the best formula for ginger, curcuma and turmeric extract jelly drinks from the results of antioxidant activity tests. This study is an experimental study using a RAL design with 1 factor, namely the ratio of ginger, curcuma and turmeric extract (1:1:1, 2:1:1, 1:2:1, and 1:1:2). Data from hedonic test results and antioxidant activity tests were analyzed using 1-factor ANOVA test and continued with Duncan test with confidence intervals <0.05. The results of the hedonic test statistical analysis showed that the proportions of ginger, curcuma and turmeric extracts had no effect on the aroma, color, taste and thickness of the jelly drink. While the results of the statistical analysis of the antioxidant activity test showed that the proportions of ginger, curcuma and turmeric extracts had an effect on the antioxidant activity of the jelly drink. The best formula is ginger, curcuma and turmeric extract jelly drink (1:2:1) with the largest antioxidant activity of 77.52%.